Hissing calls of tits elicit vigilance in feeding squirrels. Issue 6 (2nd November 2022) - Liu, Jianping; Liang, Wei
Abstract : Breeding tits in the family Paridae let out a hissing call when encountering nest predators, which is thought to be acoustic Batesian mimicry. The antipredator effect of the hissing call of Paridae has only been confirmed in several studies. To identify whether the hissing call of Japanese tits ( Parus minor ) affects the feeding behavior of the nest predator Swinhoe's striped squirrel ( Tamiops swinhoei ), we played back white noise, the call of Oriental turtle doves ( Streptopelia orientalis ), and the hissing call of Japanese tits to squirrels. The squirrels responded differently to the three types of sounds played back. The proportion of squirrels that still fed while the hissing call of tits being played (26.1%) was significantly lower than that when white noise (91.3%) and the call of doves (85.7%) being played. The alert time of feeding squirrels to the hissing call of tits was also significantly longer than that to white noise and the call of doves. Our study suggests that the hissing call of tits can change the feeding behavior of the nest predator squirrel, which may reduce nest predation in cavity birds.